Microprocessor Technology - Anderson, J. S. (John Stuart), 1941- (Oxford : Newnes, 1994)
This introductory microprocessor textbook contains information, ideas, notes, examples and circuit suggestions for assignment work. Written with reference to both the Z80 and the 6502, it caters for several FE courses.
Keywords: Microprocessors; Zilog Z-80 (Microprocessor); 6502 (Microprocessor)